The doctoral research abstracts. Vol 5: 2014 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2014)
Foreword: The fifth issue of the Doctoral Research Abstracts features the abstracts from 29 PhD doctorates receiving their scrolls in this 80th UiTM momentous convocation ceremony. The publication captures the novelty of their research and marks UiTM’s acknowledgement and tribute to the graduands whose achievement we proudly celebrate. It also reflects IGS conscientious effort to publish these abstracts which range from the discipline of science and technology, business and management to social science and humanities. To the 29 doctorates, I would like to congratulate your achievement on this auspicious occasion. This convocation is one of the important milestones in marking the course of your accomplishment. Despite all obstacles, with the support of your families and friends, this moment reflects your deserving efforts in paving your career path. On that note, on behalf of UiTM, I wish you the very best in your future undertakings and sincerely hope that you will remember and cherish the moments that you have in UiTM. May the Almighty guides us to the straight path in our endeavour for academic excellence and grant us success in this world and hereafter.